Interest of creatine supplementation in soccer - Miny, K.; Burrowes, J.; Jidovtseff, B. (Science & Sports, 2017)
Objectives: This review article aimed to summarize the current state of understanding on creatine supplementation for soccer players. In other words, it investigated the beneficial (and potentially negative) effects of this supplementation on sport-specific skills and performance in soccer players. Furthermore, this article accordingly discussed the safest and most recommended protocols for the consumption of creatine by these athletes. News: Studies have shown that creatine supplementation can have positive effects on sprint and vertical jump performances in soccer players. This supplementation may also enhance soccer players` muscle strength and adaptation to a high-intensity training regimen. Besides, creatine may be able to enhance muscle glycogen (as well as phosphocreatine) storage, reduce oxidative stress, and improve muscular repair and hypertrophy. Interestingly, creatine supplementation does not seem to affect aerobic performance. Prospects and projects: Soccer players could take creatine during pre-season training (3 to 5 g/day) in order to help them endure a high-intensity training regimen and enhance their muscular strength and adaptation resulting from strength and/or resistance training. A lower dosage (less than 3 g/day) might also be sufficient and beneficial during the season in case of fatigue, in order to sustain adequate levels of phosphocreatine and glycogen in the muscles. Occasional intakes (about 3 g) before games and/or extenuating practices could also give a physical and mental boost to the players. Conclusion: Most of the studies measured the effects of creatine on skills or physical performances in isolation from the true athletic demands of soccer match play. In conclusion, there is still a need for more research in order to determine whether creatine supplementation is ergogenic regarding the (aerobic) capacity to repeat (very) high-intensity actions, more particularly during competitive soccer.